Fragrance slow-release composite material and preparation method thereof
By mixing two -dimensional materials dispersing solution with fragrance material, and after grinding, freezing and freezing treatment, the fragrance sustained -release composite materials are prepared, which solves the problem of short fragrance fragrance. Improvement.
Patent Information
- Application Number
- CN202411481094.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
Smart Images

Figure CN119345425A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of daily chemical products, and in particular to a fragrance sustained-release composite material and a preparation method thereof. Background Art
[0002] In the prior art, the fragrance of flavors and fragrances has a short retention time and a fast volatilization speed, so how to slowly release the fragrance has become a technical problem in the field of daily chemical products technology. Summary of the invention
[0003] In view of this, the present application provides a flavor sustained-release composite material and a preparation method thereof that can solve the above-mentioned technical problems.
[0004] A method for preparing a flavor sustained-release composite material comprises the following steps:
[0005] Providing a two-dimensional material dispersion and a flavor substance, adding the flavor substance into the two-dimensional material dispersion and stirring to obtain a first mixed solution;
[0006] placing the first mixed liquid in a grinding device and grinding it to obtain a second mixed liquid;
[0007] The second mixed liquid is frozen in liquid nitrogen and then placed in a freeze dryer for freeze drying to obtain the flavor sustained-release composite material.
[0008] In some possible implementations, the two-dimensional material dispersion includes a two-dimensional material and a water-based matrix, or the two-dimensional material dispersion includes a two-dimensional material and an oil-based matrix.
[0009] In some possible implementations, the two-dimensional material is at least one of two-dimensional boron nitride nanosheets, two-dimensional titanium dioxide nanosheets, and two-dimensional mica nanosheets.
[0010] In some possible implementations, the aqueous matrix is one or more of water, sodium chloride aqueous solution, potassium chloride aqueous solution, formic acid aqueous solution, ethanol aqueous solution, acetic acid aqueous solution or sodium methoxide aqueous solution, and the oil matrix is one or more of isopropyl alcohol, liquid paraffin, caprylic / capric glyceride, jojoba oil or shea butter.
[0011] In some possible implementations, the aroma substance includes at least one of an essence and a fragrance.
[0012] In some possible implementations, in the first mixed liquid, the ratio of the solid content of the two-dimensional material in the two-dimensional material dispersion to the added amount of the aroma substance is 1:(5-10).
[0013] In some possible implementations, the grinding device is a ball mill or a sand mill.
[0014] In some possible implementations, the grinding speed is 100 to 500 rpm, and the grinding time is 12 to 48 hours.
[0015] In some possible implementations, after the step of “placing the first mixed liquid in a grinding device for grinding to obtain a second mixed liquid”, the method further includes: washing and diluting the second mixed liquid.
[0016] The present application also provides a flavor sustained-release composite material prepared according to the above preparation method, wherein the flavor sustained-release composite material comprises a two-dimensional material and a flavor substance.
[0017] In the present application, a fragrance sustained-release composite material is prepared by mixing a two-dimensional material dispersion and a fragrance substance. Due to the special size effect of the two-dimensional material and the hydrophilic / lipophilic groups introduced on the surface of the water matrix and the oil matrix, the fragrance sustained-release composite material can effectively play the role of fragrance sustained-release, and at the same time can achieve the effect of reducing penetration, so as to prevent a part of the flavors and fragrances from penetrating into the skin, thereby achieving more biosafe performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1A This is a transmission electron microscope image of hexagonal boron nitride provided in Example 1 of the present application. Figure 1B This is a scanning electron microscope image of the two-dimensional boron nitride nanosheet provided in Example 1 of the present application.
[0019] Figure 2 This is a comparison chart of the macroscopic appearance of the flavor substance used in Example 1 of the present application and the resulting flavor sustained-release composite material.
[0020] Figure 3 This is a comparison chart of infrared spectra of the flavor substance used in Example 1 of the present application and the prepared flavor sustained-release composite material.
[0021] Figure 4A and Figure 4B This is a thermogravimetric diagram of the flavor sustained-release composite material of Example 1 of the present application.
[0022] Figure 5 This is a comparison chart of the volatilization rates of the flavor sustained-release composite material provided in the examples of the present application and that of comparative example 1.
[0023] Figure 6 This is a comparison chart of the permeation rates of the flavor sustained-release composite material provided in Example 1 of the present application and that of Comparative Example 1. DETAILED DESCRIPTION
[0024] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. The reagents and materials described in the following embodiments can all be obtained from commercial sources.
[0025] The present application provides a method for preparing a flavor sustained-release composite material, comprising the following steps:
[0026] Providing a two-dimensional material dispersion and a flavor substance, adding the flavor substance to the two-dimensional material dispersion and stirring to obtain a first mixed solution;
[0027] placing the first mixed liquid in a grinding device and grinding it to obtain a second mixed liquid;
[0028] The second mixed liquid is frozen in liquid nitrogen and then placed in a freeze dryer for freeze drying to obtain a flavor sustained-release composite material.
[0029] In some embodiments, the two-dimensional material dispersion includes the two-dimensional material and an aqueous matrix, or the two-dimensional material dispersion includes the two-dimensional material and an oil matrix.
[0030] Two-dimensional materials refer to materials in which electrons can only move freely in two dimensions (planar motion) at the non-nanoscale.
[0031] In some embodiments, the two-dimensional material is at least one of two-dimensional boron nitride nanosheets, two-dimensional titanium dioxide nanosheets, and two-dimensional mica nanosheets.
[0032] In some embodiments, the sheet diameter of the two-dimensional material is 0.2-1.0 μm, for example 0.2 μm, 0.5 μm, or 1 μm.
[0033] In some embodiments, the two-dimensional material is obtained by mechanical methods, sand milling, grinding, mechanical stirring, high-speed shearing, ultrasonic treatment, high-pressure homogenization, or microfluidization to obtain two-dimensional boron nitride nanosheets, two-dimensional titanium dioxide nanosheets, and two-dimensional mica nanosheets. For example, hexagonal boron nitride powder is exfoliated into two-dimensional boron nitride nanosheets by ball milling; mica is exfoliated into two-dimensional mica nanosheets by ultrasonic treatment.
[0034] In the present application, the aqueous matrix is water or an aqueous solution containing inorganic salts or organic matter.
[0035] In some embodiments, the aqueous matrix is one or more of water, sodium chloride aqueous solution, potassium chloride aqueous solution, formic acid aqueous solution, ethanol aqueous solution, acetic acid aqueous solution or sodium methoxide aqueous solution, and the oil matrix is one or more of isopropyl alcohol, liquid paraffin, caprylic / capric glyceride, jojoba oil or shea butter.
[0036] In some embodiments, the concentration of the two-dimensional material dispersion is 0.5 to 100 mg / mL, for example, 0.5 mg / mL, 1.0 mg / mL, 5.0 mg / mL, 10.0 mg / mL, 20.0 mg / mL, 30.0 mg / mL, 40.0 mg / mL, 50.0 mg / mL, 60.0 mg / mL, 70.0 mg / mL, 80.0 mg / mL, 90.0 mg / mL or 100 mg / mL, where "concentration" refers to the mass of the two-dimensional material contained in 1 mL of aqueous matrix or oil matrix.
[0037] In some embodiments, the fragrance material includes at least one of an essence and a fragrance. For example, the fragrance material may be salvinia, isoamyl acetate, vanillin, and the like.
[0038] In some embodiments, the stirring speed of the fragrance substance and the two-dimensional material dispersion is 100 to 1000 rpm, such as 100 rpm, 200 rpm, 500 rpm, 800 rpm or 1000 rpm; the stirring time is 24 hours to 48 hours. For example, 24 hours, 30 hours, 36 hours, 42 hours or 48 hours. The stirring time within the above range is conducive to the combination of the fragrance substance and the two-dimensional material in the two-dimensional material dispersion, and is conducive to prolonging the fragrance effect.
[0039] In some embodiments, in the first mixed solution, the ratio of the solid content of the two-dimensional material in the two-dimensional material dispersion to the amount of the added flavoring substance is 1:(5-10), for example, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10. In the first mixed solution, the ratio of the solid content of the two-dimensional material in the two-dimensional material dispersion to the amount of the added flavoring substance is within the above range, which helps to ensure the fragrance retention time of the flavor sustained-release composite material.
[0040] In some embodiments, in addition to adding the fragrance substance to the two-dimensional material dispersion and stirring to obtain the first mixed solution, a silane coupling agent can also be added according to actual needs. The role of the silane coupling agent is to promote the combination of the fragrance substance and the two-dimensional material, so that the final fragrance sustained-release composite material has a longer fragrance retention time.
[0041] In some embodiments, the grinding device is a ball mill or a sand mill. The use of a ball mill or a sand mill helps to create defect sites on the surface of the two-dimensional material, and these defect sites help to bind the aroma substance to the two-dimensional material; and the use of a ball mill or a sand mill also has a certain stripping effect, which helps to further strip the two-dimensional material, so that the larger the specific surface area of the two-dimensional material, the better the effect of the two-dimensional material in adsorbing and slowly releasing the aroma substance; and the structure of the two-dimensional material will not be destroyed.
[0042] In some embodiments, the grinding speed is 100-500 rpm, such as 100 rpm, 200 rpm, 300 rpm, 400 rpm or 500 rpm; the grinding time is 12-48 hours, such as 12 hours, 24 hours, 30 hours, 36 hours, 42 hours or 48 hours. The grinding speed and time are within the above ranges, which is conducive to maintaining the two-dimensional characteristics of the two-dimensional material in the flavor sustained-release composite material, and is conducive to prolonging the fragrance retention effect of the flavor sustained-release composite material and enhancing the sustained-release effect.
[0043] The purpose of grinding the first mixed liquid in the grinding equipment is to further peel off the two-dimensional material in the first mixed liquid. In addition, it helps the aroma substance to form an interaction force with the two-dimensional material, so that the aroma substance and the two-dimensional material are adsorbed more and more tightly.
[0044] In some embodiments, after the step of "grinding the first mixed liquid in a grinding device to obtain a second mixed liquid", the step further includes: washing and diluting the second mixed liquid. The purpose of washing is to wash away the excess aroma substances in the second mixed liquid that are not combined with the two-dimensional material. The purpose of dilution is to disperse the two-dimensional material evenly to maintain the inherent properties of the two-dimensional material and to facilitate the subsequent freeze-drying step. The dilution method can be dilution with water, and the ratio of water to the second mixed liquid can be (1 to 10):1.
[0045] In some embodiments, the lyophilization time is 30 to 60 h, such as 30 h, 36 h, 42 h, 48 h, 54 h or 60 h.
[0046] The present application also provides a flavor sustained-release composite material prepared according to the above preparation method, wherein the flavor sustained-release composite material comprises a two-dimensional material and a flavor substance.
[0047] In some embodiments, in the flavor sustained-release composite material, the proportion of two-dimensional material is 20-80wt%, for example 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, and the proportion of flavor substances is 20-80wt%, for example 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%.
[0048] The following specific implementation methods will further illustrate the present application in conjunction with the above-mentioned drawings.
[0049] Embodiment 1
[0050] A method for preparing a flavor sustained-release composite material comprises the following steps:
[0051] The hexagonal boron nitride powder is exfoliated into two-dimensional boron nitride nanosheets by ball milling to obtain two-dimensional boron nitride nanosheets.
[0052] Deionized water and two-dimensional boron nitride nanosheets with a sheet diameter of 0.2 to 1.0 μm are mixed to obtain a two-dimensional boron nitride nanosheet dispersion with a concentration of 100 mg / mL.
[0053] At 25° C. and under magnetic stirring conditions, 5 g of salix sargens was added to 50 mL of a two-dimensional boron nitride nanosheet dispersion and magnetically stirred at a speed of 500 rpm for 36 h to obtain a first mixed solution.
[0054] The first mixed solution was placed in a ball mill and ball-milled at a rotation speed of 250 rpm for 24 hours to obtain a second mixed solution.
[0055] Deionized water was added to the second mixed solution to dilute it and stirred evenly, with the ratio of water to the second mixed solution being 10:1.
[0056] The diluted second mixed solution was frozen in liquid nitrogen, and then placed in a freeze dryer for freeze drying for 48 hours to obtain a flavor sustained-release composite material.
[0057] In the fragrance sustained-release composite material prepared in this embodiment, the content of the two-dimensional boron nitride nanosheets is 46.6 wt %, and the content of salvinia musk is 53.4 wt %.
[0058] Embodiment 2
[0059] A method for preparing a flavor sustained-release composite material comprises the following steps:
[0060] The titanium dioxide powder is exfoliated into two-dimensional titanium dioxide nanosheets by ball milling to obtain two-dimensional titanium dioxide nanosheets.
[0061] Deionized water and two-dimensional titanium dioxide nanosheets with a sheet diameter of 0.2 to 1.0 μm are mixed to obtain a two-dimensional titanium dioxide nanosheet dispersion with a concentration of 20 mg / mL.
[0062] At 25° C. and under magnetic stirring conditions, 5 g of isoamyl acetate was added to 50 mL of the two-dimensional titanium dioxide nanosheet dispersion and magnetically stirred at a speed of 500 rpm for 36 h to obtain a first mixed solution.
[0063] The first mixed solution was placed in a ball mill and ball-milled at a rotation speed of 250 rpm for 24 hours to obtain a second mixed solution.
[0064] Deionized water was added to the second mixed solution to dilute it and stirred evenly, with the ratio of water to the second mixed solution being 10:1.
[0065] The diluted second mixed solution was frozen in liquid nitrogen, and then placed in a freeze dryer for freeze drying for 48 hours to obtain a flavor sustained-release composite material.
[0066] In the flavor sustained-release composite material prepared in this example, the content of the two-dimensional titanium dioxide nanosheets is 47 wt %, and the content of isoamyl acetate is 53 wt %.
[0067] Embodiment 3
[0068] A method for preparing a flavor sustained-release composite material comprises the following steps:
[0069] The mica powder is exfoliated into two-dimensional mica nanosheets by ball milling to obtain two-dimensional mica nanosheets.
[0070] Deionized water and two-dimensional mica nanosheets with a sheet diameter of 0.2 to 1.0 μm are mixed to obtain a two-dimensional mica nanosheet dispersion with a concentration of 100 mg / mL.
[0071] At 25° C. and under magnetic stirring conditions, 5 g of salix sarmentosum was added to 50 mL of the two-dimensional mica nanosheet dispersion and magnetically stirred at a speed of 500 rpm for 36 h to obtain a first mixed solution.
[0072] The first mixed solution was placed in a ball mill and ball-milled at a rotation speed of 250 rpm for 24 hours to obtain a second mixed solution.
[0073] Deionized water was added to the second mixed solution to dilute it and stirred evenly, with the ratio of water to the second mixed solution being 10:1.
[0074] The diluted second mixed solution was frozen in liquid nitrogen, and then placed in a freeze dryer for freeze drying for 48 hours to obtain a flavor sustained-release composite material.
[0075] In the fragrance sustained-release composite material prepared in this embodiment, the content of the two-dimensional mica nanosheets is 46.2 wt %, and the content of salmi musk is 53.8 wt %.
[0076] Embodiment 4
[0077] A method for preparing a flavor sustained-release composite material comprises the following steps:
[0078] The hexagonal boron nitride powder is exfoliated into two-dimensional boron nitride nanosheets by ball milling to obtain two-dimensional boron nitride nanosheets.
[0079] The isopropanol is mixed with two-dimensional boron nitride nanosheets with a sheet diameter of 0.2 to 1.0 μm to obtain a two-dimensional boron nitride nanosheet dispersion with a concentration of 100 mg / mL.
[0080] At 25° C. and under magnetic stirring conditions, 5 g of salix sargens was added to 50 mL of a two-dimensional boron nitride nanosheet dispersion and magnetically stirred at a speed of 500 rpm for 36 h to obtain a first mixed solution.
[0081] The first mixed solution was placed in a ball mill and ball-milled at a rotation speed of 250 rpm for 24 hours to obtain a second mixed solution.
[0082] Deionized water was added to the second mixed solution to dilute it and stirred evenly, with the ratio of water to the second mixed solution being 10:1.
[0083] The diluted second mixed solution was frozen in liquid nitrogen, and then placed in a freeze dryer for freeze drying for 48 hours to obtain a flavor sustained-release composite material.
[0084] In the fragrance sustained-release composite material prepared in this embodiment, the content of the two-dimensional boron nitride nanosheets is 46.1 wt %, and the content of salmi musk is 53.9 wt %.
[0085] Embodiment 5
[0086] The difference between Example 5 and Example 1 is that the ball milling speed in Example 5 is 50 rpm, and the remaining steps are the same as those in Example 1.
[0087] Embodiment 6
[0088] The difference between Example 6 and Example 1 is that the ball milling speed of Example 6 is 600 rpm, and the remaining steps are the same as those of Example 1.
[0089] Embodiment 7
[0090] The difference between Example 7 and Example 1 is that the ball milling time of Example 7 is 8 hours, and the other steps are the same as those of Example 1.
[0091] Embodiment 8
[0092] The difference between Example 8 and Example 1 is that the ball milling time of Example 8 is 60 hours, and the other steps are the same as those of Example 1.
[0093] Comparative Example 1
[0094] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not contain two-dimensional boron nitride nanosheets, and the remaining steps are the same as those of Example 1.
[0095] See also Figure 1A and Figure 1B The present application conducted scanning electron microscopy tests on the hexagonal boron nitride and boron nitride nanosheets in Example 1. Figure 1A It can be seen that hexagonal boron nitride presents a large solid block structure. Figure 1B It can be seen that after ball milling, the diameter of the boron nitride sheet becomes smaller, and a two-dimensional boron nitride nanosheet is obtained.
[0096] See also Figure 2The present application also compares the appearance of the salley musk used in Example 1 and the fragrance sustained-release composite material prepared in Example 1. Figure 2 On the left is Salisbury Musk. Figure 2 The right side shows the fragrance sustained-release composite material obtained in Example 1. Generally, the application environment of fragrance substances such as flavors and fragrances is relatively fixed. If their macroscopic morphology changes significantly, it will affect their application. Figure 2 From the macroscopic appearance comparison diagram provided, it can be seen that the appearance morphology of the fragrance sustained-release composite material prepared by the preparation method of the present application is not much different from that of the salix musk itself, and does not affect the application environment of the fragrance substance.
[0097] See also Figure 3 , Figure 3 This is a comparison chart of the infrared spectra of the saliforn used in Example 1 and the fragrance sustained-release composite material prepared in Example 1, wherein curve A is the infrared spectrum of the fragrance sustained-release composite material, and curve B is the infrared spectrum of saliforn. Figure 3 It can be seen that the peak shapes of curve A and curve B are similar, indicating that no chemical change occurs in the process of making the flavor sustained-release composite material of saliforn and the two-dimensional material, that is, the composition of saliforn in the flavor sustained-release composite material does not change, and the odor it brings is consistent with that of saliforn, and will not cause the change or weakening of the fragrance. Figure 3 The change in the peak position of curve A and curve B indicates that there is an interaction between salvinia in the fragrance sustained-release composite material and the two-dimensional boron nitride nanosheets.
[0098] See also Figure 4A and Figure 4B , Figure 4A and Figure 4B This is a thermogravimetric diagram of the flavor sustained-release composite material of Example 1 of the present application, wherein: Figure 4A is the TG curve, Figure 4B is the DTG curve, Figure 4A The percentage corresponding to the horizontal stage after the curve is the mass percentage of the two-dimensional material in the flavor sustained-release composite material. Figure 4B In the figure, the peak of the curve is around 193°C, which corresponds to the weightlessness temperature of salvinia, indicating that the weightless substance is salvinia, and the remaining is the weight of the two-dimensional material.
[0099] See also Figure 5 The volatilization rates of Example 1, Examples 5 to 8 and Comparative Example 1 were measured by weighing method. Figure 5It can be seen that in the same period of time, the weight lost by the comparative example 1 is more than that of the example 1 and the examples 5 to 8, that is, the volatilization rate of the comparative example 1 is faster than that of the example 1 and the examples 5 to 8, which shows that the present application adds two-dimensional materials to compound with salix musk, and the composite fragrance sustained-release composite material obtained by compounding has a longer fragrance retention time and a slower volatilization rate than salix musk. Secondly, in the case of compounding with the two-dimensional material dispersion and salix musk, the volatilization rate of the examples 5 to 8 is faster than that of the example 1, which shows that the rotation speed and time of the ball mill will also affect the fragrance retention time and volatilization rate of the fragrance sustained-release composite material.
[0100] Figure 6 The permeation rate comparison diagram of the flavor sustained-release composite material provided in Example 1 of the present application and the comparative example 1, wherein curve A represents the permeation rate of the flavor sustained-release composite material provided in Example 1 of the present application, and curve B represents the permeation rate of the comparative example 1. Figure 6 It can be seen that the fragrance sustained-release composite material provided in the present application can achieve the effect of reducing penetration, so as to prevent a part of the flavors and fragrances from penetrating into the skin, thereby achieving a more biosafe performance.
[0101] The safety of the materials of Examples 1 to 8 and Comparative Example 1 was determined by blind patch testing with volunteers. The results are shown in Table 1.
[0102] Table 1.
[0103] Group Security Embodiment 1 Safety Embodiment 2 Safety Embodiment 3 Safety Embodiment 4 Safety Embodiment 5 Safety Embodiment 6 Safety Embodiment 7 Safety Embodiment 8 Safety Comparative Example 1 Safety
[0104] It can be seen from the test results in Table 1 that the fragrance sustained-release composite material prepared according to the preparation method provided in the present application is safe and has the potential to be applied to daily chemical products.
[0105] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A method for preparing a flavor sustained-release composite material, characterized in that: The following steps are involved: Providing a two-dimensional material dispersion and a flavor substance, adding the flavor substance into the two-dimensional material dispersion and stirring to obtain a first mixed solution; placing the first mixed liquid in a grinding device and grinding it to obtain a second mixed liquid; The second mixed liquid is frozen in liquid nitrogen and then placed in a freeze dryer for freeze drying to obtain the flavor sustained-release composite material.
2. The method for preparing the flavor sustained-release composite material according to claim 1, characterized in that: The two-dimensional material dispersion includes a two-dimensional material and a water-based matrix, or the two-dimensional material dispersion includes a two-dimensional material and an oil-based matrix.
3. The method for preparing the flavor sustained-release composite material according to claim 2, characterized in that: The two-dimensional material is at least one of two-dimensional boron nitride nanosheets, two-dimensional titanium dioxide nanosheets, and two-dimensional mica nanosheets.
4. The method for preparing the flavor sustained-release composite material according to claim 2, characterized in that: The aqueous matrix is one or more of water, sodium chloride aqueous solution, potassium chloride aqueous solution, formic acid aqueous solution, ethanol aqueous solution, acetic acid aqueous solution or sodium methoxide aqueous solution, and the oil matrix is one or more of isopropyl alcohol, liquid paraffin, caprylic / capric glyceride, jojoba oil or shea butter.
5. The method for preparing the flavor sustained-release composite material according to claim 1, characterized in that: The aroma substance includes at least one of essence and fragrance.
6. The method for preparing the flavor sustained-release composite material according to claim 1, characterized in that: In the first mixed liquid, the ratio of the solid content of the two-dimensional material in the two-dimensional material dispersion to the added amount of the aroma substance is 1:(5-10).
7. The method for preparing the flavor sustained-release composite material according to claim 1, characterized in that: The grinding equipment is a ball mill or a sand mill.
8. The method for preparing the flavor sustained-release composite material according to claim 1, characterized in that: The grinding speed is 100 to 500 rpm, and the grinding time is 12 to 48 hours.
9. The method for preparing the flavor sustained-release composite material according to claim 1, characterized in that: After the step of "placing the first mixed liquid in a grinding device and grinding it to obtain a second mixed liquid", the method further includes: washing and diluting the second mixed liquid.
10. A flavor sustained-release composite material obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The fragrance sustained-release composite material comprises a two-dimensional material and a fragrance substance.
Citation Information
Patent Citations
Nano-structured silicate, functionalised forms thereof, preparation and uses
CN101142140A
High polymer material with controllable smell releasing function and preparation method of high polymer material
CN109435344A
Slow-release natural plant aromatic functional paint
CN110305369A
Slow-release natural plant aromatic functional paint
CN110305522A
Heat conduction type slow-release essence and cigarette product
CN114532589A